Analysis of Compliance With the Consumption of Fe Tablets Among Female Adolescents at Sman 1 Kalapanunggal, Sukabumi Regency, in 2025 - Nurmalasari, Mia; Trina Arlym, Lisa; Rukmaini (Rajaki of Tulip Medika Publisher, 2025)
Background: Anemia in adolescent girls can reduce immunity, reduce activity, academic achievement, and fitness. FE supplementation is one way to address this issue. Teenagers lack motivation to consume FE supplements. Analyzing FE supplementation factors is one strategy to address this issue.Purpose: This study aims to analyze factors that can influence compliance with FE supplement consumption in female adolescents at SMAN 1 Kalapanunggal, Sukabumi Regency in 2025.Methodology: This study used a cross-sectional approach. The population in this study was 415 female students, the sample in this study was 100 female students. The sampling technique used Cluster Random Sampling. The research instrument was a questionnaire. The questionnaire was tested for validity and reliability with a Cronbach's alpha coefficient value of 0.716. Bivariate analysis used the Chi-Square test. Results: The bivariate analysis showed a significant relationship between knowledge, peer support, and parental support with adherence to FE supplement consumption. There was no significant relationship between school support and health worker support with adherence to FE supplement consumption. The variable with the strongest relationship with adherence to FE supplement consumption was knowledge with an OR of 9.179.Conclusion: There is a relationship between knowledge, peer support, and parental support with adherence to FE supplement consumption. There is no significant relationship between school and health worker support and adherence to FE supplement consumption. The variable with the strongest relationship with adherence to FE supplement consumption is knowledge with an OR of 9.179. Keywords:Anemia; Adolescent girls; FE tablets; compliance; knowledge; Support.